1998
DOI: 10.1055/s-2007-973551
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Visual Impairment in Periventricular Leukomalacia*

Abstract: Infants with cerebral palsy (CP) frequently present cerebral visual impairment (CVI) often caused by damage to retrochiasmatic pathways. This is particularly true of subjects with damage to the periventricular white matter. Thirty-eight preterm infants with periventricular leukomalacia (PVL) diagnosed by MRI were examined to correlate binocular visual acuity with neuroradiological findings. Binocular visual acuity was evaluated using Teller Acuity Cards and a complete ophthalmological examination was also perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
4
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 3 publications
5
67
4
2
Order By: Relevance
“…1 Specifically, the prevalence of visual impairments, such as strabismus, ocular motor apraxia, nystagmus, optic atrophy, restriction of the visual field, 2,3 defective color vision, 4,5 and reduced grating acuity 4,5 range from 66% to 94% in these children. 6,7 The treatment and long-term care of the affected children consist of a huge burden and cost to the family, professionals, and society. The above-mentioned visual impairments in those brain-damaged infants have been mainly attributed to occipital lesions in the brain.…”
mentioning
confidence: 99%
“…1 Specifically, the prevalence of visual impairments, such as strabismus, ocular motor apraxia, nystagmus, optic atrophy, restriction of the visual field, 2,3 defective color vision, 4,5 and reduced grating acuity 4,5 range from 66% to 94% in these children. 6,7 The treatment and long-term care of the affected children consist of a huge burden and cost to the family, professionals, and society. The above-mentioned visual impairments in those brain-damaged infants have been mainly attributed to occipital lesions in the brain.…”
mentioning
confidence: 99%
“…24,25 . Lanzi et al 26 found a correlation between reduction of VA and reduction of the peritrigonal white matter as well as the extent of calcarine atrophy. Reduction of the volume of the peritrigonal white matter on MRI has been reported to correlate with impairment of visual perception in children with spastic diplegia.…”
Section: Discussionmentioning
confidence: 98%
“…76 The territorial distributions and neurologic consequences of perinatal retrogeniculate injury reflect the developing brain's level of maturity at the time of injury (Table 1.1). 34,37,38,91,144,174,265,280,281,349,599 In the full-term infant, the brain receives its vascular supply primarily from the major cerebral arteries, and its watershed areas lie at the interfaces between the major cerebral arterial distributions. 35,174,599 Mild degrees of term hypoxic-ischemic injury produce watershed infarctions in the arterial border zones (i.e., the parieto-occipital and parasagittal cortex), injuring both gray and white matter, usually resulting in encephalomalacia.…”
Section: Cortical Visual Insufficiencymentioning
confidence: 99%
“…36,99,265,281 Neuroimaging abnormalities in these children are frequently confined to subcortical white matter (optic radiations and corticospinal tracts) as opposed to the cortical gray matter injury that predominates in term anoxia. 32,35,36,144,174,265,280,281,341,349,599 Preterm injury to the developing brain that primarily injures subcortical white matter produces PVL. 76 PVL is usually seen in ventilator-dependent premature infants who survive longer than a few days.…”
Section: Subcortical Visual Loss (Periventricular Leukomalacia)mentioning
confidence: 99%
See 1 more Smart Citation